The Effectiveness of the Pragmatic Perception of the Argumentative Scales in the Combat Verses of the Holy Qur’an - Hasan, Issa Qasim; Al-Najjar, Ashwaq Mohammed Ismaiel (Al-Adab Journal, 2022)
The aim of this research is to study the argumentative scales in the noble combat verses, and to show the effectiveness of pragmatic perception in reaching the objectives of the Qur’anic discourse; this is because the recipient's awareness of the intent is the goal of every discourse, and it depends on the speaker's influence, persuasion, and guidance. The context of the research study necessitated to showing the peaceful nature of the Qur’anic discourse, as it is described as gradual, beginning with argumentative premises, and ending with results, and how the speaker progresses in his discourse in a gradual, peaceful manner. To be more influential in the recipient, the research deals with the characteristic of peace among Arab scholars in their various disciplines. This is to show the style they dealt with this feature in their sciences, even if they did not use specific conventions for it, and to indicate the points of convergence between what they opted to, and what the Westerners found in their studies of the argumentative scales on the grounds that they were the founders of this theory. Then, the research moves on to the practical side by analyzing holy verses from the research blog. This is to show how the Qur’anic discourse advances its arguments until it reaches the intended result, which is the desired end of the discourse to reach the process of influence and persuasion. It was found that the arguments in the noble combat verses were arranged in a hierarchical style, forming a wonderful argumentation. This is due to the fact that the Holy Qur’an, by its nature, is not satisfied with presenting one argument, but rather gradually presents all the arguments in order to influence and persuade the recipient. This is to either refute and invalidate the arguments of the unbelievers, or to raise the determination of the believers, and encourage them to wage jihad for the sake of God Almighty.